Primary health care attributes assessment: children and adolescents living with HIV - Bibiana Sales Antunes; Stela Maris de Mello Padoin; Cristiane Cardoso de Paula (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objectives: To evaluate the attributes derived from Primary Health Care (PHC) focusing on children and adolescents living with HIV, in the experience of health professionals, comparing traditional units (BHU) and Family Health Strategy (FHS). Method: Cross-sectional research in which 524 professionals from 25 cities of Rio Grande do Sul, Brazil were interviewed. The Primary Care Assessment Tool Brazil was used from March through August 2014. Results: The PHC score attributed to FHS (7.8) was higher than that attributed to BHU (6.8). The higher scores contributed to the home visit, the professional qualification and the employment bond, the latter acting independently of the others. Conclusion: The satisfactory evaluation of the derived attributes approves the interaction with users and community and the potential of PHC to attend these children and adolescents, and the home visit qualifies the practice.